RELATIONSHIP SMOKING HABITS OF FAMILY MEMBERS AND NUTRITIONAL STATUS OF INFANTS WITH ACUTE RESPIRATORY INFECTION EVENT ON INFANTS (Case study in the work Area of Larangan Public Health Center of Larangan District, Pamekasan Regency) - Afriyani Noviyana; Nurhaidah .; Hadi Suryono (Poltekkes Kemenkes Surabaya, 2013)
Acute Respiratory infection (ARI) is one of the causes of infant mortality in developingcountries, including in Indonesia. This study aimed to investigate the relationship betweensmoking habits of family members and nutritional status of infants with ARI incidence ofinfants in the larangan Public Health Center.This type of research was an observational case control study desiqn, The sample wasmostly infants of ARI patients in Larangan District who have come to the Larangan PublicHealth Center during the last three months that were 53 infants and 53 infants were notsuffered ARI who were neighbors of infans who suffered ARI. Data analysis was performedusing Chi Square test with a = 0,05.Results of this study shown that smoking habits of fdamily members (p = 0,243) thereis no association with incidence of acute respiratory infection of infant, while the nutritionalstatus of infants (p = 0,008) is correlated with the incidence of acute respiratory infection oninfants.It is recommended that larangan public health center to improve the provision ofinformation of the public about the nutritional status of infants in order to avoid acuterespiratory diseases, providing enough food for infants by providing fruit that are around theenvironment such as bananas and papayas, maintain the condition or the air in the house tostay healthy by cleaning the house every day, behave healthy lifestyle, and care sanitation inorder not to become breeding grounds for germsKeywords: ARI, smoking habits, nutritional status